(untitled) (Research, Society and Development, 2021)
The umbu is an especially important plant source for the Caatinga, as it has important compounds for food. Spirulina spp. is used as a functional food supplement. In the present study, the objective was to elaborate and evaluate the physical-chemical characteristics of the liqueurs of the leaves and fruits of umbu plus Spirulina spp. obtained at the Federal Institute of Alagoas, located in the municipality of Piranhas - AL. Four formulations of liquor from the umbu leaf and four formulations of liquor from the umbu pulp were added, added by Spirulina spp. Then, the physical characterization of 20 fruit samples was carried out by measuring the fruit’s mass, length, diameter, density, and pulp yield. For the physical-chemical characterization of the liquors, analyzes of pH, total titratable acidity, soluble solids, moisture, and ashes were carried out. The liqueurs of umbu leaves and umbu pulp showed average pH levels between 2.93 to 3.01, respectively. Among the formulations, we can see that the humidity was high, getting more than 90%. From these results, the capacity of these liquors in agro-industrial processing was observed, as they have high yields. And that the inclusion of Spirulina spp. enhances the nutritional value of the liquor, with high sensory acceptance by potential consumers.